A SWARA-COPRAS approach to the allocation of risk in water and sewerage public–private partnership projects in Malaysia - Valipour, Alireza; Yahaya, Nordin; Noor, Norhazilan MD; Valipour, Iman; Tamošaitienė, Jolanta (International Journal of Strategic Property Management, 2019)
In a situation of growing water demand, inadequate public funding, poor asset condition and lack of maintenance in developing countries, public-private partnerships (PPPs) play an important role in the development of infrastructure, such as water supply and sewerage services. The purpose of this study is to develop a quantitative approach to appropriate risk allocation, with attention directed to the impact of positive and negative factors in water and sewerage projects. The paper presents a hybrid SWARA-COPRAS approach to examine risk allocation, particularly for PPP water supply and sewerage projects in the context of Malaysia. In addition to PPP infrastructure projects, the approach has the potential to be adapted to other applications. The proposed method enables decision makers to utilise qualitative linguistic terms in the allocation of risk between the public and private sector, and to select the best strategy for risk allocation in a contract. Finally, 24 significant risks were identified: six risks would preferably be allocated to the public sector, while seven risks would be assigned to the private sector, and eleven risks would preferably be shared by both parties. The finding from this study can help the government of Malaysia to determine an attractive political strategy for private investors to support a PPP water and sewerage infrastructure project.